Factors Associated with COVID-19 Infection, Hospitalization and Death in New York City Neighborhoods - Anna Gu; Hira Shafeeq; Ting Chen; Preety Gadhoke (University of Minnesota Libraries Publishing, 2021)
Background: A key to an effective Coronavirus 2019 (COVID-19) Community Intervention is to understand populations who are most vulnerable to it. We aimed at evaluating characteristics of New York City communities where rates of confirmed COVID-19 cases were particularly high. Methods: The study outcomes - neighborhood-specific confirmed COVID-19 cases, positive tests, and COVID-19 attributable deaths were calculated using data extracted from the New York City government health website, which were linked to results from Community Health Survey. Distributions of study outcomes across New York City community districts and their associations with neighborhood characteristics were examined using Jonckheere-Terpstra tests. Results: As of May 21, 2010, rates of confirmed cases ranged from 0.8% (Greenwich Village and Soho) to 3.9% (Jackson Heights), and the rates of attributable death from to 0.6‰ (Greenwich Village and Soho) to 4.2‰ (Coney Island). Higher percentages of black, Hispanic and foreign-born populations, lower educational attainment, poverty, lack of health insurance, and suboptimal quality of health care were all factors found to be correlated with increased rates of confirmed COVID-19 cases.  Conclusions: The epidemiology of COVID-19 exhibited great variations among neighborhoods in New York City. Community interventions aimed at COVID-19 prevention and mitigation should place high priorities in areas with large populations of blacks and Hispanics and economically disadvantages areas.